Group and individual assignment - Chegenizadeh, Amin; Nikraz, Hamid (International Association of Computer Science and Information Technology Press, 2012)
This paper investigates the effect of group and individual assignments toward better learning. For this purpose, different types of assignments were used. Finally, the feedbacks from students are presented in result section. The students’ feedbacks proved that using team work method was more popular compare to individual one. The students also preferred working on analytical assignment rather than theoretical one.